2×2 Dominant achievement goal profiles in high-level swimmers - Fernandez-Rio, J.; Cecchini Estrada, J. A.; Mendez-Giménez, A.; Fernández-Garcia, B.; Saavedra, P. (European Journal of Sport Science, 2014)
The goal of this study was to assess achievement goal dominance, self-determined situational motivation and competence in high-level swimmers before and after three training sessions set at different working intensities (medium, sub-maximal and maximal). Nineteen athletes (males, n=9, 18.00±2.32 years; females, n=10, 16.30±2.01 years, range = 14-18) agreed to participate. They completed a questionnaire that included the Dominant Achievement Goal assessment instrument, the 2×2 Achievement Goals Questionnaire for Sport (AGQ-S), The Situational Motivation Scale (SIMS) and the Competence subscale of the Basic Psychological Needs in Exercise questionnaire (BPNES). Results indicated that participants overwhelmingly showed mastery-approach achievement goal dominance, and it remained stable at the conclusion of the different training sessions under all intensity levels. This profile was positively correlated to self-determined situational motivation and competence. However, swimmers' feelings of competence increased only after the medium intensity level training session. After the completion of the maximal intensity training session, swimmers' self-determined motivation was significantly lower compared to the other two training sessions, which could be caused by a temporary period of burnout. Results indicated that high-level swimmers had a distinct mastery-approach dominant achievement goal profile that was not affected by the workload of the different training sessions. They also showed high levels of self-determined situational motivation and competence. However, heavy workloads should be controlled because they can cause transitory burnout